CFAP300 mutation causing primary ciliary dyskinesia in Finland - Schultz, Rüdiger; Elenius, Varpu; Fassad, Mahmoud R.; Freke, Grace; Rogers, Andrew; Shoemark, Amelia; Koistinen, Tiina; Mohamed, Mai A.; Lim, Jacqueline S. Y.; Mitchison, Hannah M.; Sironen, Anu I. (Frontiers in Genetics, 2022)
Primary ciliary dyskinesia (PCD) is a rare genetic condition characterized by chronic respiratory tract infections and in some cases laterality defects and infertility. The symptoms of PCD are caused by malfunction of motile cilia, hair-like organelles protruding out of the cell and being responsible to remove mucus from the airways and organizing inner organ positioning during embryonic development. PCD is caused by mutations in genes coding for structural or assembly proteins in motile cilia. Thus far mutations in over 50 genes have been identified and these variants explain 70% of all known cases. Population specific genetics behind PCD has been reported, thus underlining the importance of characterizing gene variants in different populations for development of gene-based diagnostics. In this study, we identified a loss-of-function mutation in CFAP300 gene causing lack of the protein product. PCD patients with the identified CFAP300 mutation have immotile airway epithelial cilia, which is caused by missing dynein arms in ciliary axonemes. Furthermore, we demonstrate that CFAP300 is transported along cilia in normal human airway epithelial cells suggesting a role for CFAP30 in dynein complex transport in addition to preassembly in the cytoplasm. Our results highlight the importance of CFAP300 in dynein arm assembly and improve diagnostics of PCD in Finland.